One- and two-photon responsive injectable nano-bundle biomaterials from co-assembled lipopeptides for controlling molecular diffusion. Issue 32 (31st July 2019) - Wang, Dong; Hou, Xiaojun; Zhang, Xuecheng; Zhao, Yurong; Sun, Yawei; Wang, Jiqian
Abstract : An injectable NB biomaterial. Abstract : An injectable biomaterial has been prepared through co-assembly of lipopeptides C4 –Bhc–Glu–Glu–NH2 and C14 –Phe–Lys–Lys–NH2 . This biomaterial contained a large number of nanofibre bundles (nano-bundles, NBs) of lipopeptide co-assemblies and performed like hydrogels. The morphologies of the NBs were observed by transmission electron microscopy (TEM) and atomic force microscopy (AFM). The rheological properties were investigated with a rheometer. Excitingly, the NB biomaterials exhibited shear thinning and self-healing properties, and could be used as injectable biomaterials. The coumarin group in the lipopeptides endowed the NB biomaterials with both ultraviolet (UV, a one photon process) and near-infrared (NIR) light (a two photon process) responsiveness. A small molecule (Doxorubicin, DOX) and a large molecule (bovine serum albumin, BSA) were used as model drugs, and both of them could be encapsulated in the NB biomaterials and could also be released sustainably or explosively under different conditions (with or without one- and two-photon irradiation). DOX and BSA have different release behaviors because of the NBs. Cell assays showed that the co-assembled NB biomaterials exhibited low cytotoxicity to normal cells. However, when DOX was loaded, the NB biomaterials could kill HeLa cells sustainably. Under UV and NIR irradiation, HeLa cells could be killed rapidly because of the burst release of DOX. The co-assembled supramolecular NB biomaterials with dual-responsiveness, tunable rheological properties and multi-drug encapsulating ability might have potential in biomedical engineering.